Mandatory Disclosure of Managerial Contracts in Nonprofit Organizations - Michael Kopel; Marco A. Marini (Fondazione Eni Enrico Mattei (FEEM), 2020)
Nonprofit organizations have been recently mandated to disclose the details of their executives' compensation packages. Contract information is now accessible not only to current and prospective donors, but also to rival nonprofit organizations competing for donations in the fundraising market. Our aim is to investigate the impact of publicly available contract information on fundraising competition of nonprofit organizations. We argue that, although such provision makes contract information available to multiple stakeholders and increases the transparency of the nonprofit sector, it also induces nonprofits to use managerial incentive contracts strategically. In particular, we find that the observability of incentive contracts relaxes existing fun draising competition. This is beneficial in terms of nonprofits' outputs, in particular when these organizations are trapped in a situation of excessive fundraising activities. However, we show that publicly available contract information distorts nonprofits' choice of projects, thus potentially inducing socially inefficient project clustering.
Keywords: L31; D64; F35; L13; 330; Nonprofit Organizations; Mandatory Contract Disclosure; Fundraising Competition; Strategic Incentive Contracts; Project Clustering; Project Specialization